IMPLEMENTASI PENDIDIKAN KARAKTER PADA PEMBELAJARAN TEMATIK DI KELAS IV SD NEGERI 24 BETUNG KABUPATEN BANYUASIN - Jumiati, Jumiati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This study aims to describe the values of character, the implementation of character education, and obstacles in implementing character education on thematic learning in grade V SD Negeri 24 Betung. This research uses qualitative approach with descriptive type. The subject of this research is the fourth grade teacher. This research was conducted at SD Negeri 24 Betung in January 2018-March 2018. Data collection techniques used were observation, interview, and documentation. The main instrument is the researcher by using the tool in the form of observation guidance, interview, and document analysis. Data were analyzed using Miles and Huberman model that is data reduction, data presentation, and conclusion. Technique examination of data validity with technique triangulation. The results showed that the implementation of character education consists of planning and implementation. Lesson planning used is not made by the teachers themselves, but has already shown the integration of character education. In terms of implementation, teachers implement it through learning activities and learning methods, spontaneous activities, discipline planting, and create a conducive atmosphere. In thematic learning the teacher develops and instill nine values of characters developed. Obstacles faced by teachers in implementing character education are the limited facilities and infrastructure in the form of learning media, learning methods, attitude assessment, and family factors.